Metabolic variation in Cistus monspeliensis L. ecotypes correlated to their plant-fungal interactions. (August 2020) - Salomé-Abarca, Luis Francisco; Mandrone, Manuela; Sanna, Cinzia; Poli, Ferruccio; van der Hondel, Cees A.M.J.J.; Klinkhamer, Peter G.L.; Choi, Young Hae
Abstract: The effect of environmental factors on the chemical composition of plants eventually resulting in plant growth regulation is an age-old issue in plant biology. Nowadays, the acceleration in changes in environmental conditions (e.g. global warming) can act as an incentive to investigate their correlation with metabolic changes. In this study, Cistus monspeliensis plants grown on the island of Sardinia (Italy) were used to explore the geographical-mediated metabolic variation and its repercussion on plant-fungus interactions. Samples of different ecotypes of C. monspeliensis were collected and chemically profiled by 1 H NMR and HPTLC-based metabolomics and the relationship between the variations of biological activity was examined by multivariate data analysis. The ecotypes, collected from different geographical zones and altitudes, exhibited clearly distinguishable chemical profiles, particularly in their terpene and phenolic contents. In particular, multivariate data analysis revealed several diterpenes of the labdane and clerodane series among the terpenes and methoxyflavonoids to be responsible for the differentiation. The antifungal activity of the plants was used to explore the correlation between chemical variation and biological activity. Results showed that there was a strong correlation between the metabolic profiles and the antifungal activity, revealing terpenes and methoxylated flavonoids as the main involved metabolites. This demonstrated that environmental factors can influence the chemical variation of plant ecotypes, resulting in the generation of chemotypes that are potentially adapted to their niche conditions including the plant-fungal interactions. Graphical abstract: Image 1 Highlights: Ecotypes of C. monspeliensis were chemically profiled by 1 H NMR/HPTLC-metabolomics. 1 H NMR showed the general metabolic variation and HPLTC did for targeted one. Diterpenoids and flavonoids caused the chemical variation of the ecotypes. Diterpenoids mainly caused the variation of the ecotypes' antifungal effects. Methoxylated flavonoids could provide additive effects to a diterpenoid.